PENGARUH FASHION INVOLVEMENT DAN SHOPPING LIFESTYLE TERHADAP IMPULSIVE BUYING KONSUMEN DI TOKO BUTIK BANDUNG PASIR PENGARAIAN - Hodma Joli; Seprini (Jurnal Ilmiah Cano Ekonomos, 2018)
This study aims to determine the effect of fashion involvement and shopping lifestyle on impulsive buying of consumers at the Boutique Store in Bandung Pasir Pengaraian. The population of this study were all buyers at Boutique Bandung, amounting to 39,167 people with a total sample taken of 100 people. The sampling method uses accidental sampling technique. The analysis technique used is multiple linear regression analysis using the SPSS program. The results of the study based on multiple linear regression analysis showed that fashion involvement and shopping lifestyle towards impulsive buying consumers in Bandung Boutique Store Pasir Pengaraian with a coefficient of 1.109. The conclusion of this study is both the partial test and the simultaneous fashion involvement and shopping lifestyle variables on impulsive buying consumers.